Análisis del crecimiento del frijol (Phaseolus vulgaris L. var ´Turrialba-4´) cultivado en solución nutritiva - Ascencio, J.; Fargas Arroyo, J.E. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
The present work has as a main objective to analize the growth of the bean plant (Phaseolus vulgaris L. ´Turrialba-4´) through its growth indexes. The plants were grown in Hoagland´s nutrient solution No. 2 and ramdomly arranged on tables ina greenhouse conditioned for this system of culture and provided with appropriate climatological apparatus. The basic data for the calculation of the growth indexes (dry weight and leaf area) were obtained from the five plants sampled weekly. The principal parameters used to evaluate the growth of the plants were the Relative Growth Rate (RGR), the Net Assimilation Rate and the Leaf Area Ratio (LAR) wich were calculating using Blackman´s methodology of growth analysis, regression and correlation. It was established that the efficiency of the bean plant, considered as a whole, depended on the LAR an a high number of leaves per plant. Furthermore the RGR reached a mean value of 0.69 g/g/week, the NAR 0.35 g/g/week and the Leaf Area Ratio 1.79 dm2/g.